A short review of the most common safety concerns regarding creatine ingestion - Longobardi, Igor; Solis, Marina Yazigi; Roschel, Hamilton; Gualano, Bruno (Frontiers in Nutrition, 2025)
Creatine monohydrate supplementation is widely used for enhancing athletic performance and improving clinical outcomes, but concerns regarding its safety persist, particularly relating to risk of cancer, impaired kidney function, dehydration, and gastrointestinal issues. This short review critically evaluates these concerns based on current scientific evidence. Although some theoretical risks, such as creatine’s potential to form carcinogenic compounds, have been discussed, the available research does not support a link between creatine supplementation and cancer. In terms of kidney health, studies consistently show no adverse effects on renal function in healthy individuals, though caution is advised for those with pre-existing kidney conditions and pregnant women, as evidence is lacking for these populations. Claims that creatine leads to dehydration or muscle cramps during exercise are largely unsupported by controlled studies, which demonstrate no significant effects on hydration or thermoregulation; in fact, creatine may reduce the incidence of muscle cramps and assist in maintaining thermoregulatory balance. Gastrointestinal distress is reported in some individuals, particularly at high doses, but such effects are dose-dependent and not universally experienced. Overall, the evidence suggests that creatine monohydrate supplementation is generally safe when used appropriately, with further research needed to understand its impact on specific populations.